2006
DOI: 10.1128/mcb.26.1.28-38.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SIRT1 Catalytic Activity Increases p53 Acetylation but Does Not Alter Cell Survival following DNA Damage

Abstract: Human SIRT1 is an enzyme that deacetylates the p53 tumor suppressor protein and has been suggested to modulate p53-dependent functions including DNA damage-induced cell death. In this report, we used EX-527, a novel, potent, and specific small-molecule inhibitor of SIRT1 catalytic activity to examine the role of SIRT1 in p53 acetylation and cell survival after DNA damage. Treatment with EX-527 dramatically increased acetylation at lysine 382 of p53 after different types of DNA damage in primary human mammary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
366
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(393 citation statements)
references
References 60 publications
24
366
3
Order By: Relevance
“…EX527 showed the higher SIRT1 inhibitory activity (IC 50 = 0.38 μmol/L) and SIRT2 inhibitory activity (IC 50 = 32.6 μmol/L) compared with Sirtinol and Salermide, whereas nicotinamide had relatively low potency against SIRT1 with an IC 50 of 85.1 but potently inhibited SIRT2 (IC 50 = 1.16 μmol/L). These in vitro SIRT1/2 inhibition results are generally in consensus with the previously published data on the efficacy of some of these SIRT inhibitors on SIRT1 and SIRT2 (26,27,36). However, these in vitro data could not completely explain for the failure of EX527 to induce cell death, as EX527 has higher SIRT2 inhibitory activity than Sirtinol and higher SIRT1 inhibitory activity compared with Sirtinol and Salermide yet does not induce cell death.…”
Section: Sirt Inhibitors Display Potent In Vitro Sirt1/2 Inhibitory Asupporting
confidence: 86%
“…EX527 showed the higher SIRT1 inhibitory activity (IC 50 = 0.38 μmol/L) and SIRT2 inhibitory activity (IC 50 = 32.6 μmol/L) compared with Sirtinol and Salermide, whereas nicotinamide had relatively low potency against SIRT1 with an IC 50 of 85.1 but potently inhibited SIRT2 (IC 50 = 1.16 μmol/L). These in vitro SIRT1/2 inhibition results are generally in consensus with the previously published data on the efficacy of some of these SIRT inhibitors on SIRT1 and SIRT2 (26,27,36). However, these in vitro data could not completely explain for the failure of EX527 to induce cell death, as EX527 has higher SIRT2 inhibitory activity than Sirtinol and higher SIRT1 inhibitory activity compared with Sirtinol and Salermide yet does not induce cell death.…”
Section: Sirt Inhibitors Display Potent In Vitro Sirt1/2 Inhibitory Asupporting
confidence: 86%
“…It has been previously described that inhibition of SIRT1 catalytic activity enhances p53 lysine 382 acetylation after DNA-damaging agents. 13 In replicate wells, MCF-7 cells were treated with Ex-527, Ex-243 and the inactive enantiomer Ex-242 overnight for 12 h. In the continued presence of Ex-527, Ex-243 or Ex-242, cells were then exposed to the DNA-damaging agent etoposide to induce p53 acetylation for 6 h. Lysates were immunoblotted with an anti-acetyl p53 Lys-382 antibody or p53 antibody. p53 acetylation was enhanced in the presence of the potent and selective SIRT1 inhibitors Ex-527 and Ex-243 but not the control inactive enantiomer Ex-242.…”
Section: Resultsmentioning
confidence: 99%
“…The discovery and characterization of these compounds are described elsewhere. 13 For all experiments, a 10 mM stock solution of each compound in DMSO was prepared and stored at À80 1C until use.…”
Section: Chemicalsmentioning
confidence: 99%
“…It is therefore worth noting that none of the cancer cell lines used in this study expresses functional p53. Furthermore, SIRT1 does not exert protective effect after DNA damage in all cell types (Solomon et al, 2006), and cytoplasm-localized SIRT1 has even been reported to enhance apoptosis (Jin et al, 2007). Thus the subcellular localization, expression and activity levels of SIRT1 are essential for its effect on cell survival (Deng, 2009;Liu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%